REPRESENTASI KEMANDIRIAN PEREMPUAN DALAM KONTEN PENDAKI FURKY SYAHRONI DI MEDIA SOSIAL - Zainal Abidin Achmad; Anita Anita (LPPM Universitas Negeri Surabaya, 2025)
This study aims to analyze the representation of women's independence and resilience in Furky Syahroni's social media content, which features her as an Indonesian female climber at the international level. The primary focus of this research is how narrative, visual, and symbolic strategies in TikTok, Instagram, and YouTube video uploads construct the image of women as independent, courageous, and break through gender stereotypes in extreme activities such as mountain climbing. This study uses a qualitative method with a thematic analysis of TikTok, Instagram, and YouTube content by Furky Syahroni during the period 2019–2024. Secondary data were obtained from literature, online interviews, personal blogs, and podcasts featuring Furky Syahroni. The results show that social media has become a new space for women to build a positive, equal identity in the public sphere. Furky Syahroni’s content contains educational, motivational, and courageous messages that can inspire other women to transcend social boundaries. The novelty of this research lies in the study of gender communication on the virtual platform in the context of extreme physical activities. This research contribution enriches the discourse on gender equality in digital media and demonstrates the potential of social media for women's empowerment.